Study of marsh foraminifera from the coastal plain of Buenos Aires (Argentina) and its ecological implications - Ballesteros-Prada, Angélica; Bernasconi, Emiliana (Zootaxa, 2019)
The objective of this work was determinate the diversity and abundance of benthic foraminifers from recent sediments of Channel 15, Samborombón Bay (35º57´–35º58´S and 57º25´–57º22´W). From this analysis, we identified 31 species grouped within 17 genera. The assemblages were composed mainly of hyaline and agglutinated forms characterized by Elphidium aff. poeyanum, Elphidium gunteri, Ammonia parkinsoniana, Arenoparella mexicana and Trochammina inflata, reflecting an environment of marsh or floodplain. The foraminifer’s tests were generally well preserved, with morphologies that indicate predominantly epifauna and epifauna-infauna. The present work shows that despite having a general fauna characteristic of these environments, there are small microenvironments that are characterized by the state of preservation, diversity and abundance of the found specimens. In that context, three associations were recognized; A, dominated by Astrononion sp.1 that was registered in the central part of the channel; association B, characterized mainly by E. aff. poeyanum that was founded in the internal and external areas of the channel and association C, characterized by a considerable increase of mentioned agglutinated species (close to 50%) registered in the center of the channel. This study represents one of the first contributions on the distribution of foraminifera and their ecological characteristics from recent sediments in Samborombón Bay.